The effects of auditory satellite navigation instructions and visual blur on road hazard perception. (April 2019) - Lacherez, P.; Virupaksha, S.; Wood, J.M.; Collins, M.J.
Highlights: Examined hazard perception in presence of blur and auditory navigation instructions. 20 drivers (age 29.4 ± 3.2 years) completed a Hazard Perception Test. Defined blur levels introduced after correcting individual refractive error. Auditory navigation instructions were also presented in half of the trials. Blur and instruction both slowed participants' response times to potential hazards. Abstract: The distracting effects of mobile telephone use while driving are well known, however the effects of other sources of distraction, such as auditory navigation devices, are less well understood. Whether the effects of auditory distraction might interact with other sensory impairments, such as vision impairment, is of interest given that visual impairment is relatively common within the population, particularly as a result of uncorrected refractive error. In this experiment, 20 current drivers (mean age of 29.4 ± 3.2 years), binocularly viewed video recordings of traffic scenes presented as part of the Hazard Perception Test and responded to potential hazards within the traffic scenes. Half of the presented scenes included auditory navigation instructions as an auditory distractor. Additionally, some of the scenes were viewed through optical lenses to induce different levels of refractive blur (+0.50 DS, +1.00 DS and +2.00 DS). Hazard perception response times increased significantly (p < 0.05) with increasing blur. Participants were significantly slower in reacting to hazards for the +1.00 DS and +2.00 DS blur conditions compared to the control condition (with no blur). There was also a significant increase in response times to hazards in the presence of the auditory navigation instructions. The combined effect of blur and auditory instructions was additive, with the worst performance being in the presence of both blur and auditory instructions. These results suggest that the delivery of auditory navigation guidance for those with visual impairments, such as blur, which are relatively common in the population, should be further investigated.